# Algebra

Find the difference quotient and simplify your answer. Step by step. f(x) = 3x2 − 6x, f(x + h) − f(x) h , h ‚ 0

1. f(x)=3x^2-6x
f(x+h)=3(x+h)^2 -6(x+h)
= 3x^2+6xh+3h^2-6x-6h

so f(x+h)-f(x)= 0x^2-0x+6xh-3h^2-6h

dividing that by h then
6x-3h-6
as h approaches zero, then the difference quotent= 6x-6

posted by bobpursley

## Similar Questions

1. ### math

An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made
2. ### math

An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made
3. ### MATH

Hannah is showing her work in simplifying (6.1 − 4.5) − 2.5 + 3.9. Identify any error in her work or reasoning. Step 1: (6.1 − 4.5) − 2.5 + 3.9 Step 2: 6.1 + (− 4.5 − 2.5) + 3.9 (associative
4. ### Help needed- PreCalc

Please help me understand how to solve this questions. I need step by step solution and answer because I find it difficult to understand when someone on here writes the answer instead of showing step by step work on how he/she got
5. ### Calculus--complex numbers

let z= a+bi be a complex number. it is given that the quotient (z-i)/(z-1) is purely imaginary. show that z lies on a circle and determine the centre and radius of this circle. OK, here's my working out...( i am using "X" as my
6. ### math

10a) Simplify the expression and explain each step. 12 + 3(2y – 3) Step 1: apply distributive property Step 2: combine like terms Step 3: simplify b) Factor the expression completely. 18b – 12 What is the GCF of 18 and 12? Use
7. ### Math

Find the derivative of y=(sinx/(1+cosx))^2. I used the chain rule, but the second part involved the quotient rule which gives a very complicated expression that u do not know how to simplify. Could you please give me a detailed
8. ### Math

Simplify the difference quotient [f(2 + h) − f(2)]/h if h ≠ 0. f(x) = x^2 − 3x I keep getting the answer wrong...please help.
9. ### college

Evaluate the difference quotient for the given function. Simplify your answer. f(x) = 3 + 5x − x2, f(4 + h) − f(4) h
10. ### Pre-Calc

Simplify the difference quotient [f(2 + h) − f(2)]/h ; if h ≠ 0. f(x) = x2 − 3x I keep getting the answer wrong. I must be messing up my steps...Please Help

More Similar Questions